RANCANGAN TEKNIS VERTICAL GARDEN KAWASAN STASIUN KOTA BOGOR JAWA BARAT - Andrianto Kusumoarto; Rahmat Rejoni (Universitas Indraprasta PGRI, 2020)
Bogor City is a city that has some places for tourist. The Bogor City station area is one of the most active areas, especially during working days and hours. The motorized vehicle circulation path is one of the very dense circulation routes. The aims of this study is to design a vertical garden around the Bogor Station area. The activity method used is descriptive qualitative method. The Bogor City Government builds comfortable pedestrian paths and regulates pedestrian movement routes, for example installing road dividers between vehicle circulation lanes, placing vertical gardens and fences to separate pedestrian paths from motorized vehicle lanes, building JPOs (Pedestrian Bridges). The two-way motorized vehicle circulation path is separated by a median of the road where a portion of the fence has been placed by a vertical garden. This technical design activity was carried out at the median of Kapten Muslihat road at the junction segment of Ir. H. Djuanda road, intersection of the red bridge and front and back view of the JPO fence. For pedestrian paths, there are several paths that have been installed vertical gardens on the dividing fence between the vehicle lane and the path. Besides having aesthetic value, the existence of this route also functions as a barrier for pedestrians entering the station. The path of this path continues towards Major Oking road